WordGirl. Word up - Serwacki, Anita (Kaboom!, 2012)
"The City's favorite daughter fights the good fight against bad vocabulary in another round of thrilling adventures! What will WordGirl and Captain Huggy Face do against a wave of mobilized vittles? The Butcher creates motorized mayhem in 'The Ham Van Makes the Man,' and it would take a dastardly duo like Chuck the Evil Sandwich-Making Guy and Dr. Two-Brains to make the world's most evil grilled cheese sandwich. What will our heroes do?"--Publisher.